1999
DOI: 10.3758/bf03211960
|View full text |Cite
|
Sign up to set email alerts
|

The discrimination of heading from optic flow is not retinally invariant

Abstract: Three experiments were conducted to determine whether the discrimination of heading from optic flow is retinally invariant and to determine the importance of acuity in accounting for heading eccentricity effects. In the first experiment, observers were presented with radial flow fields simulating forward translation through a three-dimensional volume of dots. The flow fields subtended 10°of visual angle and were presented at 0°, 10°,20°, and 40°of retinal eccentricity. The observers were asked to indicate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Various researchers have claimed that given optical flow, only the central visual field is necessary for accurate judgments of heading and velocity (Atchley & Andersen, 1999;Crowell & Banks, 1993;Warren & Kurtz, 1992). However, because these researchers were interested mainly in showing that optical flow cues were not constant across the retina, most of the studies relied mainly on standard computer displays with relatively small FOVs and did not document the utility of peripheral optical flow cues in cognitive map formation tasks.…”
Section: Optical Flowmentioning
confidence: 99%
“…Various researchers have claimed that given optical flow, only the central visual field is necessary for accurate judgments of heading and velocity (Atchley & Andersen, 1999;Crowell & Banks, 1993;Warren & Kurtz, 1992). However, because these researchers were interested mainly in showing that optical flow cues were not constant across the retina, most of the studies relied mainly on standard computer displays with relatively small FOVs and did not document the utility of peripheral optical flow cues in cognitive map formation tasks.…”
Section: Optical Flowmentioning
confidence: 99%
“…Various researchers have claimed that, given optical flow, only the central visual field is necessary for accurate judgments of heading and velocity [3,7,36,37]. However, most of these studies relied mainly on standard computer displays with relatively small fields of view.…”
Section: Optical Flow In Navigationmentioning
confidence: 99%
“…Declines in motion coherence, created by the addition of random motion, impairs the processing of such stimuli [Zanker and Hupgens 1994]. Aging has been associated with increases in optic flow heading thresholds, thought to be attributable to declines in central visual processing [Warren, Jr. et al 1989] [Atchley and Andersen 1998] [Atchley and Andersen 1999]. However, comparison to other forms of visual motion processing have shown that optic flow perception is relatively resistant to the detrimental effects of both brain aging [Billino et al 2008] and focal cortical lesions [Billino et al 2009].…”
Section: Introductionmentioning
confidence: 99%